ANALISIS MUSIK IRINGAN TARI JEPIN SENGGAYONG DESA MEDAN JAYA KECAMATAN SIMPANG HILIR KABUPATEN KAYONG UTARA - Arianda yarso; Imam Ghozali; Chiristianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated there is uniqueness of the vocal melody of the accompaniment songs of Jepin Senggayong dance from Kayong Utara Regency has been the researcher's interest in carrying out this study directed at describing the aspects of the music. Theories used for the study were the structures, elements, musicology, rhythm patterns, forms, and the chords of the music. This is qualitative research using the descriptive-analytic method with musicology approach. the data were gathered from the interviews and observation on the researched accompaniment music, of which the data were collected using observation, direct communication, and documentary study techniques. Along with interview and observation guides, the researcher acted as the main instrument of research. The data were validated by extended observation and triangulation techniques and were analyzed by data reduction, presentation, and conclusion. The findings show that the accompaniment of Jepin Senggayong music is music consiting of twoparts that comprise two sentence. The tempo used ranges from 90 or 110. In the vocal section three are also ornaments with two forms of music which includetwo sentences with three phrasesand six motifs.This study suggests the reactivation of traditional artists to preserve their traditional music and dance as part of the culture, particularly in the Kayong Utara Regency, Kalimantan Barat. Keywords: Analysis, Accompaniment Music, Jepin Senggayong Dance